Cognitive Counseling with Modelling Krisna and Bisma to Improve Self Achievement - I Komang Jaya Riana; I Ketut Dharsana; Luh Putu Sri Lestari (Department of Guidance and Counseling, FIP, Undiksha, 2017)
This study aims to Determine the Influence of Cognitive Behavioral Counseling Theory With Lord Krishna Basu Modeling Technique To Improve Self Achievement Through Lesson Study In X-1 Students In Sma Negeri 1 Sukasada. This type of research is quasi-experimental research design with